The validity in performance measures used in hospital planning - Leotta, Antonio; Ruggeri, Daniela; Castro, Monica (Proceedings of Pragmatic Constructivism, 2017)
The present research aims to discuss the theoretical conditions for validity in performance measures used in hospital planning. In doing so, the research draws on a new emerging research paradigm, called Pragmatic Constructivism (Nørreklitet al., 2010). It conceives of accounting as a social reality constructed through the integration of four ontological dimensions: facts, possibilities, values and communication. The conditions for validity in performance measures used in hospital planning are examined drawing on Nørreklit et al. (2007). Specifically we investigate theoretical conditions for validity in accounting performance measurement, analysing the ontological and epistemological nature of accounting data. The theoretical framework is applied to interpret the empirical evidence coming from a case of an Italian hospital located in the south of Italy. The empirical results showed how the theoretical framework helps to better understand the validity in some of the performance measures contained in the hospital plans: the validity of knowledge of past results is examined by verifying the correspondence of performance measures with the past activity of the hospital; while the validity of the estimations of future results is analysed by verifying their coherence and consistency.